The effects of blood flow restriction training on post activation potentiation and fatigue level: systematic review with meta-analysis - Zeng, Nannan; Liu, Haiyang; Wang, Jian; Jiang, Lizhu (Frontiers in Physiology, 2025)
ObjectiveThis study aims to comprehensively explore the effects of blood flow restriction (BFR) training on the post-activation potentiation (PAP) and the rating of perceived exertion (RPE) through meta-analysis, so as to provide a scientific basis for athletes’ physical fitness training.MethodsThe PubMed, CNKI, Web of Science and EBSCO databases were searched to look for randomized controlled trials (RCTs) on the effects of BFRT on post-activation potentiation (PAP) and the rating of perceived exertion (RPE). The Cochrane risk of bias tool was used to screen the literature. With the help of Revman 5.4 and Stata 17.0 software, the literature quality assessment and statistical analysis were completed. Meanwhile, sensitivity analysis and funnel plots were utilized to examine the stability of the results and the publication bias.ResultsA total of 31 related studies were included, among which 22 studies focused on the relationship between BFR training and PAP, covering 347 participants. Meta-analysis showed that BFRT could significantly affect PAP [SMD = 0.49, 95% CI (0.20, 0.77), P = 0.0008]. When the testing method was Squat Jump [SMD = 1.35, 95% CI (0.40, 2.30), P < 0.0005], the exercise intensity was 40%–70% 1RM [SMD = 1.21, 95% CI (0.69, 1.73), P < 0.0001], and the compression intensity was ≤50% AOP [SMD = 0.77, 95% CI (0.24, 1.30), P = 0.05], the effects on PAP reached the maximum, respectively, and were statistically significant. In terms of the impact of BFR training on RPE, 18 studies with 238 subjects were included. BFR training could significantly increase the RPE of the subjects [SMD = 1.21, 95% CI (0.69, 1.73), P < 0.0001]. When the exercise mode was Knee flexion [SMD = 0.65, 95% CI (0.18, 1.11), P = 0.0006], the exercise intensity was Mixed oxygen Training [SMD = 1.03, 95% CI (0.50, 1.56), P = 0.0001], and the compressive strength was ≥60% AOP [SMD = 0.75, 95% CI (0.02, 1.48), P = 0.05], a more significant effect size was presented.ConclusionBlood flow restriction training can induce the occurrence of post-activation potentiation (PAP). BFR exercises with 40%–70% 1RM and ≤50% AOP are more likely to stimulate PAP. Meanwhile, BFR training will significantly affect the rating of perceived exertion (RPE). BFR training under mixed oxygen training and with a compressive strength of ≥60% AOP has a stronger perception of fatigue.Systematic Review Registration:http://inplasy.com, identifier INPLASY202430008.